2013
DOI: 10.1002/2013jb010466
|View full text |Cite
|
Sign up to set email alerts
|

Subducted slabs stagnant above, penetrating through, and trapped below the 660 km discontinuity

Abstract: [1] A new P wave tomographic model of the mantle was constructed using more than 10 million travel times. The finite-frequency effect of seismic rays was taken into account by calculating banana-donut kernels at 2 Hz for all first arrival time data, and at 0.1 Hz for broadband differential travel time data. Based on this model, a systematic survey for subducted slab images was developed for the circum-Pacific; including the Kurile, Honshu, Izu-Bonin, Mariana, Java, Tonga-Kermadec, southern and northern South A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
474
3
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 476 publications
(508 citation statements)
references
References 78 publications
(100 reference statements)
29
474
3
2
Order By: Relevance
“…%; Irifune, 1994), dominates the viscosity of this region (Girard et al, 2016). Seismic observation suggests that some slabs stagnate at 600-1000 km depths (Fukao and Obayashi, 2013). Since there are no phase transitions in this region, some special explanations are required.…”
Section: Geochemical Implicationsmentioning
confidence: 98%
“…%; Irifune, 1994), dominates the viscosity of this region (Girard et al, 2016). Seismic observation suggests that some slabs stagnate at 600-1000 km depths (Fukao and Obayashi, 2013). Since there are no phase transitions in this region, some special explanations are required.…”
Section: Geochemical Implicationsmentioning
confidence: 98%
“…The plumes also rise in a nearly vertical fashion from the CMB, not what would be expected if vigorous convection of the lower mantle were present (see Hand, 2015). Indeed, there had already been evidence that descending lithospheric slabs stall out near the 1000 km depth (Fukao et al, 2013). Lastly, pinching and shearing in the plumes as they reached the 1000 km depth suggested that the plumes are thermochemical plumes, i.e., composed of different material than the surrounding mantle (for a discussion of thermochemical plumes, see Kumagai et al, 2008).…”
Section: Earthquakes and Mantle Plumes In Earth Expansionmentioning
confidence: 96%
“…Yoshida and Hamano 2015 , Yoshida, 20141 1970Forsyth and Uyeda, 1975, Gerya, 2011Forsyth and Uyeda 1975 P 660 km 1000 km Fukao and Obayashi, 2013660 km , Fukao et al, 2009Yoshioka and Naganoda, 2010Yoshida, 2013Alvarez, 1982, 1990 …”
Section: Yoshida and Hamano 2015mentioning
confidence: 99%